Rozwój biografistyki i regionalistyki powstania styczniowego na Białorusi w historiografii polskiej okresu międzywojennego: The Development of Biography Studies and Regional Studies of the 1863–1864 Uprising in Belarus in Polish Historiography of the Interwar Period - Matveichyk, Dzmitry (Przegląd Wschodnioeuropejski, 2019)
The scope of the study is historiography development in interwar Poland (1918– 1939), in particular, the accumulation of facts and the development of value judgments about the 1863–1864 Uprising on the territory of Belarus. The analysis was conducted on the basis of the Biography Studies and Regional Studies of the Uprising, published during the mentioned period (books, scientific and popular articles in magazines and newspapers). It shows that the area of these studies was actively developing during the interwar twenty years, which resulted in the creation of about 70 publications. However, the Polish historians at that time were not able to overcome political bias, introduce a large number of documentary sources and generally to turn to large-scale integrated scientific researches.